2017
DOI: 10.1177/1933719116678692
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Circulating Progenitor Cells and Endothelial Colony-Forming Cells Are Decreased in Preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disease characterized by the new onset of hypertension and proteinuria. Mothers with PE are known to develop endothelial dysfunction, but its effect on infants has been understudied, as newborns are often asymptomatic. Recent studies indicate that infants born from preeclamptic pregnancies develop endothelial dysfunction including higher blood pressure during childhood and an increased risk of stroke later in life. We hypothesize that PE reduces the number and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…A relevant clinical example is the pathway by which maternal preeclampsia contributes to the risk of chronic lung disease in the newborn [ 5 ]. The effects of preeclampsia (exposure A) on the developing lung (outcome Y) are mediated by disruptions in angiogenesis (mediator M), indicated by altered pro-angiogenic umbilical cord blood biomarkers [ 4 , 13 ]. However, preterm birth (measured confounder C) may confound the mediator-outcome relationship, as the degree of prematurity is associated with both severe lung disease [ 9 ] and levels of pro-angiogenic biomarkers [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relevant clinical example is the pathway by which maternal preeclampsia contributes to the risk of chronic lung disease in the newborn [ 5 ]. The effects of preeclampsia (exposure A) on the developing lung (outcome Y) are mediated by disruptions in angiogenesis (mediator M), indicated by altered pro-angiogenic umbilical cord blood biomarkers [ 4 , 13 ]. However, preterm birth (measured confounder C) may confound the mediator-outcome relationship, as the degree of prematurity is associated with both severe lung disease [ 9 ] and levels of pro-angiogenic biomarkers [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…49 Decreased numbers of endothelial progenitor cells have been demonstrated in the cord blood of preterm newborns who develop BPD, 50,51 cells which are also decreased in maternal diabetes and pre-eclampsia. 52,53 Interestingly, cord blood from pregnancies with a placenta that demonstrated severe maternal vascular under-perfusion had lower levels of placental grow factor (PIGF), granulocyte-colony stimulating factor (G-CSF) and VEGF-A. 34 This pattern was consistent in cord blood of those infants who were later diagnosed with BPD complicated by echocardiographic findings of PH, but only the relationship with PIGF and G-CSF held up in a validation cohort.…”
Section: Potential Mechanisms Of Placental Diseasementioning
confidence: 92%
“… Circulating progenitor cell (CPC) flow cytometry gating strategy adapted from Gumina et al ( 23 ) . Here, peripheral blood mononuclear cells were analyzed by polychromatic flow cytometry.…”
Section: Epc Isolation Via Flow Cytometrymentioning
confidence: 99%
“…With regard to preeclampsia, different groups of investigators have demonstrated both reductions in circulating number and abnormal function of ECFCs isolated from the venous cord blood of babies born to preeclamptic mothers ( 23 , 32 , 33 ). Specifically, Gumina et al showed a decrease in both pro- and non-angiogenic subsets of CPCs identifiable by flow cytometry in pregnancies complicated by preeclampsia in comparison to normotensive controls.…”
Section: Umbilical Cord Blood Epcs and Diseasementioning
confidence: 99%
See 1 more Smart Citation